2008
DOI: 10.5007/2175-7925.2008v21n3p163
|View full text |Cite
|
Sign up to set email alerts
|

Novas espécies de aves para o Estado de Santa Catarina, sul do Brasil

Abstract: ResumoO conhecimento ornitológico em Santa Catarina aumentou consideravelmente nas últimas duas décadas, e com freqüência são realizadas adições à avifauna catarinense ou redescobertas de espécies com registros históricos. Desta forma, apresentamos os primeiros registros e localidades de ocorrência de Phimosus infuscatus, Accipiter poliogaster, Porzana fl aviventer, Picumnus cirratus e Polioptila lactea em Santa Catarina. Unitermos: Phimosus infuscatus, Accipiter poliogaster, Porzana fl aviventer, Picumnus cir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
2
0
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 4 publications
2
2
0
2
Order By: Relevance
“…Since then, there has been no more detailed information for the municipality, even though the species presents a local population, daily movements, forages in urban and rural areas, and breeds in local rivers, aspects here documented for the first time. The data presented here contributes to the knowledge of the species and its recent expansion, recorded by Rupp et al (2008) and Piacentini et al (2009).…”
Section: Discussionsupporting
confidence: 66%
See 2 more Smart Citations
“…Since then, there has been no more detailed information for the municipality, even though the species presents a local population, daily movements, forages in urban and rural areas, and breeds in local rivers, aspects here documented for the first time. The data presented here contributes to the knowledge of the species and its recent expansion, recorded by Rupp et al (2008) and Piacentini et al (2009).…”
Section: Discussionsupporting
confidence: 66%
“…Until 2003, surveys of the species in southern Brazil had been carried out in Paraná (Scherer-Neto & Straube, 1995) and Rio Grande do Sul (Belton, 1994;Sick, 1997;Dias & Burger, 2005;Guadagnin, Peter, Perello, & Maltchik, 2005;Silva, 2006;Acosta et al, 2010), but not in Santa Catarina, the state between them (Rupp et al, 2008;Piacentini et al, 2009), even though it was also expected to be found there (Rosário, 1996). However, P. infuscatus began to be reported in the state from 2003 onwards, in an accelerated colonization, with movement from south to north and east to west until the current occupation of almost the entire state (Rupp et al, 2008;Piacentini et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Vem se tornando cada vez mais rara na sua área de distribuição (BirdLife International, 2009). Registros atuais concentram-se no Paraguai e no nordeste da Argentina, áreas do oeste do Paraná e no Rio Grande do Sul (Bencke et al 2003) e em Santa Catarina no Parque Nacional da Serra do Itajaí, município de Indaial e município de Apiúna (Rupp et al, 2008). No Rio Grande do Sul, Belton (1994) a registrou em Garruchos, Iraí e Fazenda do Umbu.…”
Section: Aves Ameaçadas Registradas Em Iraíunclassified
“…Segundo a lista da fauna ameaçada para o Estado de Santa Catarina (CONSEMA, 2011), são 97 espécies de aves ameaçadas, sendo 28 na categoria de criticamente em perigo, 31 em perigo e 38 vulnerável. É importante ressaltar que o acréscimo no número de espécies ameaçadas de extinção não somente está relacionado como as intervenções antrópicas, mas também, pelo aumento no nível de conhecimento ornitológico, causado pelos inúmeros levantamentos realizados no estado nos últimos anos (GHIZONI-JR, 2004;AZEVEDO, GHIZONI-JR, 2005;SILVA, 2006;AMORIM;PIACENTINI, 2006;RUPP et al, 2008;GHIZONI et al, 2009;GROSE, 2011), possibilitando estabelecer um diagnóstico mais preciso de cada espécie.…”
Section: Introductionunclassified